2016
DOI: 10.1167/iovs.16-19442
|View full text |Cite
|
Sign up to set email alerts
|

Optic Nerve Head Morphology in Nonarteritic Anterior Ischemic Optic Neuropathy Compared to Open-Angle Glaucoma

Abstract: Citation: Fard MA, Afzali M, Abdi P, et al. Optic nerve head morphology in nonarteritic anterior ischemic optic neuropathy compared to open-angle glaucoma. Invest Ophthalmol Vis Sci. 2016;57:4632-4640. DOI:10.1167/ iovs.16-19442 PURPOSE. To compare optic nerve head (ONH) morphology of optic nerve atrophy between eyes with primary open-angle glaucoma (POAG) and eyes with a history of nonarteritic anterior ischemic optic atrophy (NAION) using enhanced depth imaging (EDI) with spectraldomain optical coherenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 37 publications
2
30
2
Order By: Relevance
“…Hata et al 10 showed that eyes with compressive optic neuropathy had a smaller LC depth than eyes with glaucoma without accounting for the role of choroidal thickness. In another study, we also found that ALD is deeper in glaucomatous cupping than in ischaemic optic neuropathy 13. However, in this study we first found similar posterior displacement of the LC surface and equally deep ALD in NGC and glaucomatous cupping after adjusting for age and axial length.…”
Section: Discussioncontrasting
confidence: 45%
See 1 more Smart Citation
“…Hata et al 10 showed that eyes with compressive optic neuropathy had a smaller LC depth than eyes with glaucoma without accounting for the role of choroidal thickness. In another study, we also found that ALD is deeper in glaucomatous cupping than in ischaemic optic neuropathy 13. However, in this study we first found similar posterior displacement of the LC surface and equally deep ALD in NGC and glaucomatous cupping after adjusting for age and axial length.…”
Section: Discussioncontrasting
confidence: 45%
“…The mean of three measurements was defined as the average central prelaminar thickness (PLT) (figure 1D). 13 …”
Section: Methodsmentioning
confidence: 99%
“…Surprisingly, the few published studies have shown conflicting results, suggesting either thinning9 or, on the opposite, thickening of the PCT in NAION eyes,34 35 and sometimes in the healthy, opposite eyes, compared with controls. The choroid may be also thinner at the subfoveal level in eyes with NAION, compared with controls, after adjusting for age, optic disc diameter, gender and refractive error 8.…”
Section: Discussionmentioning
confidence: 96%
“…We also previously showed thick prelaminar tissue using EDI-OCT in NAION eyes comprises a component of crowded optic discs in such eyes. 23,24 It is possible that PPCMv may be increased in NAION, but OCT-A may lack sensitivity to identify such a change, if present. There may be insufficient resolution of compacted vessels in the tight parapapillary space.…”
Section: Discussionmentioning
confidence: 99%